Polymer-based spherical activated carbon – ultrafiltration (UF-PBSAC) for the adsorption of steroid hormones from water: Material characteristics and process configuration. (15th October 2020) - Tagliavini, Matteo; Weidler, Peter Georg; Njel, Christian; Pohl, Julia; Richter, Dennis; Böhringer, Bertram; Schäfer, Andrea I.
Highlights: A thin PBSAC layer on the permeate side of UF removes steroid hormones effectively. A millimetric packed-layer reaches estradiol removal higher than 99%. The use of smaller PBSAC particles within the layer enhances the adsorption kinetics significantly. Estradiol concentration can be reduced to value lower than the proposed drinking water guideline. Abstract: The European Union has proposed the value of 1 ng L − 1 as a drinking water quality standard for estradiol. With conventional technologies only partially removing estradiol, the investigation of novel alternatives is more than ever required. Tagliavini and Schäfer proposed that the use of a thin activated carbon layer combined with a membrane is worth considering. In this work, the process was further advanced through a systematic investigation of the role of activated carbon size, activation and surface chemistry on the removal of estradiol. The use of smaller carbon particles allows reaching the ambitious target value of 1 ng L − 1 in a millimetric layer. Further, adsorption kinetic enhancement by increasing the oxygen content on the carbon improves the removal from 96 to 99 % (for a layer of 2 mm) for OH-containing pollutants such as estradiol. High removal, together with low pressure and no by-product formation, are characteristics that make the UF-PBSAC a promising and competitive approach. Graphical abstract: Image, graphical abstract